Efektif terapi wound bed preparation terhadap waktu penyembuhan luka pada pasien diabetes melitus tipe 2 - Suprapti, Tuti; Herawati, Ade Tika (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Wound Bed Preparation (WBP), a modern approach focusing on wound cleansing, infection control, moisture balance, and edge stimulation, has proven globally effective but is not yet widely and systematically implemented or studied in Indonesia. Purpose: This study aimed to assess the effectiveness of the Wound Bed Preparation (WBP) therapy on wound healing time in T2DM patients compared to standard wound care methods. Method: A quasi-experimental study with a pretest-posttest control group design was conducted. The sample consisted of 30 patients divided into two groups (intervention and control). Wound evaluation was performed using the Bates-Jensen Wound Assessment Tool (BWAT) on day 0, day 7, and day 14. The respondents' age ranged from 45 to 83 years, with 63.3% being male. Results: The effectiveness of wound healing showed a -value of on day 7 and a highly significant -value of on day 14. Clinically, by day 7, a significant positive response was observed in the intervention group, including the emergence of a 'minimal severity' category and a decrease in the number of 'critical' wounds, indicating an improvement in the wound bed quality through debridement, infection control, and moisture management. Although the distribution of severity categories on day 14 appeared similar to day 0, a notable decrease in BWAT scores within those categories demonstrated structural improvement in the wounds. Conclusion: Wound Bed Preparation (WBP) is effective in improving the quality of the wound bed and is recommended to be adopted as a standard approach in diabetic wound care. Keywords: BWAT; Diabetes Mellitus; Diabetic Ulcer; Wound Bed Preparation; Wound Healing. Pendahuluan: Terapi Wound Bed Preparation (WBP) yang berfokus pada pembersihan luka, pengendalian infeksi, menjaga kelembapan, dan stimulasi tepi luka menjadi pendekatan modern yang terbukti efektif secara global, namun belum banyak diimplementasikan dan dikaji di Indonesia secara sistematis. Tujuan: Menilai efektivitas terapi Wound Bed Preparation terhadap waktu penyembuhan luka pada pasien DM tipe 2 dibandingkan dengan metode perawatan luka standar. Metode: Penelitian quasi-eksperimen dengan pretest-posttest control group. Sampel terdiri dari 30 pasien yang dibagi menjadi dua kelompok (intervensi dan kontrol). Evaluasi dilakukan menggunakan BWAT (Bates-Jensen Wound Assessment Tool) pada hari ke-0, ke-7, dan ke-14. Hasil: Efektifitas penyembuhan luka pada hari ke 7 dengan p Value 0.91 pada hari ke 14 efektifitas 0.000, Diskusi pada hari ke-7 terjadi perubahan klinis yang bermakna, yaitu munculnya kategori keparahan minimal dan penurunan jumlah luka kritis. Hal ini menunjukkan adanya respons positif terhadap penerapan WBP, terutama melalui proses debridement, pengendalian infeksi, dan manajemen kelembapan yang mampu memperbaiki kualitas dasar luka. Sedangkan pada hari ke-14, meskipun kategori keparahan luka tampak serupa dengan hari ke-0, penurunan skor BWAT dalam kategori tersebut menunjukkan adanya perbaikan struktural pada luka. Simpulan: WBP efektif dalam memperbaiki kualitas dasar luka dan layak dijadikan pendekatan standar dalam perawatan luka diabetes. Kata Kunci: BWAT; Diabetes melitus; Penyembuhan luka; Ulkus Diabetikum; Wound Bed Preparation.